AgriTech4Morocco Innovation Challenge Acceleration workbook for one-on-one tutorial sessions - Menza, Gianpiero; Zaccari, Claudia (2023)
The Alliance of Bioversity International and CIAT and its Accelerate for Impact Platform (A4IP) developed a methodology to scout science-based technologies in the early stage, addressing sustainable agriculture and climate action, and connect them with CGIAR to maximize delivery and impact. This methodology involves eight project phases, including the assessment, design, launch, call for applications and selection, bootcamp, acceleration program and demo day, post-acceleration support, and dissemination. As part of the F2R-CWANA, A4IP is conducting innovation challenges in three countries (Morocco, Uzbekistan, and Egypt) to source, support, and accelerate AgriFood and ClimateTech solutions that can provide concrete, deployable, and sustainable solutions for value chain actors, and help respond to the inefficiencies of the agriculture sector in these specific countries. A4IP selects relevant industry players and partners to support the co-design, organization, and implementation of the innovation challenge through equity-free funding, mentoring, technology guidance, access to networks, and/or payment of university tuition fees.